PERANAN VISUALISASI DALAM PEMBELAJARAN GERAK - Sukadiyanto Sukadiyanto (Jurnal Kependidikan, 2000)
The purpose of this research is to study contribution of visualization in motor learning. The research population is male and female  athletes in Yognkarta. The random sampling technique is utilized to select athletes as the sample of this research. This is a survey research and the data was collected by question- noire technique. There are three  (visual, auditory, and Hnesthetic) in each questionnoire. The results of this research factors  indicated that the contribution of auditory  visual  factor  is 46.91%o, and kinesthetic  factor  is 0.24o/o, factor is 52.85%o. The Iargest contribution in visualization among those from  the Hnesthetic  factor.  factors  The general conclusion is tlwt learning sport activities need all of those factors,  but kinesthetic is the most essential one.. The reason is that learning through direct various experiences will be mueh better than through obseryation. In learning sport sHlls, it is necessary to provide feedback  and use audio visual media as aids.